Use of Denosumab in Children With Osteoclast Bone Dysplasias: Report of Three Cases. (22nd August 2019) - Upfill‐Brown, Alexander; Bukata, Susan; Bernthal, Nicholas M; Felsenfeld, Alan L; Nelson, Scott D; Singh, Arun; Wesseling‐Perry, Katherine; Eilber, Fritz C; Federman, Noah C
ABSTRACT: Denosumab has been used successfully to treat disease‐associated osteoclast overactivity, including giant cell tumor of bone. Given its mechanism of action, denosumab is a potent potential treatment of other osteoclast bone dysplasias including central giant cell granuloma (CGCG), aneurysmal bone cyst (ABC), and cherubism. Relatively little is known about the safety and efficacy of denosumab in patients with these conditions, especially in children. We report on 3 pediatric patients treated with denosumab over a 3‐year period at UCLA Medical Center (Los Angeles and Santa Monica, CA, USA): a 12‐year‐old with recurrent ABC of the pelvis, a 14‐year‐old with CGCG of the mandible, and a 12‐year‐old with cherubism. All were started on a 1‐year course of 15 doses 120 mg s.c., given monthly with two loading doses on day 8 and 15. All patients demonstrated rapid and pronounced clinical improvement while on denosumab, including a significant reduction in pain and sclerosis of lytic lesions on radiographs. Within 1 month of initiating therapy, 2 patients experienced hypocalcemia (Common Terminology Criteria for Adverse Events [CTCAE] grade 2) and hypophosphatemia, with 1 patient experiencing symptoms. One patient went on to experience symptomatic rebound hypercalcemia (CTCAE grade 4) 5 months after completing therapy, requiring bisphosphonates and calcitonin. For the second patient, we developed a schedule to wean denosumab involving the progressive lengthening of time between doses from 1 to 4 months in 1‐month increments before cessation. We found that denosumab therapy results in significant clinical and radiographic improvement for pediatric patients with nonresectable ABC, CGCG, and cherubism. Problems with serum calcium may be more common in younger patients, with symptomatic and protracted rebound hypercalcemia after cessation of therapy the most significant. We present a potential solution to this problem with progressive spacing of doses. Potential serious adverse events from alterations in calcium homeostasis should be explored in prospective clinical trials. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.